Influence of Youth Self-Help Group Members Skills on Group Performance in Aldai Constituency, Nandi County, Kenya. - Kiprotich, Peter; Wangaruro, Dr. Jane; Nyachieo, Dr. Gladys (International Journal of Scientific Research and Management (IJSRM), 2018)
The study focused on the effects of acquired skills through education and training on the performance of youth Self-Help Groups (SHG). A multi stage sampling was used to get a sample of 136 youth SHG members who participated in the study from the 56 youth groups that were sampled out. Other key informants were also interviewed. Structured questionnaires and interviews were used in collecting data, which was analysed using appropriate descriptive techniques. The study results revealed that there were no positive relationship between the the level of education and the performance of youth SHGs. It was found that inadequate skills, ignorance and limited finances were some of the challenges affecting youth SHGs. The study recommends a follow up and involvement of local leaders and experts on the implementation of youth programmes.